2017
DOI: 10.1016/j.apjtm.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Lipase inhibitory activity of Lagenaria siceraria fruit as a strategy to treat obesity

Abstract: The study suggests that Lagenaria siceraria has potential to inhibit pancreatic lipase activity, suppressing lipid digestion and thereby diminishing entry of lipids into the body. Regular intake of aqueous decoction of the fruit may therefore be recommended for control of obesity. Fatty acids and their esters may play role as inhibitors of lipase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 14 publications
3
29
0
2
Order By: Relevance
“…In addition, CME contains anti-hyperglycemic compounds, furanoeudesma-1,3-diene and 2-O-acetyl-8,12-epoxygermacra-1 [37] and has stimulatory effect on β cells division and insulin secretion [18,65]. Benzofuranebisindole hybrids have been shown to have in vitro antioxidant effect and in vivo anti-dyslipidemic activity as it decreases total cholesterol, triglycerides and phospholipids through increasing the plasma lecithin cholesterol acyltransferase activity, which plays a key role in lipoprotein metabolism increasing HDL-C in serum level [66].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CME contains anti-hyperglycemic compounds, furanoeudesma-1,3-diene and 2-O-acetyl-8,12-epoxygermacra-1 [37] and has stimulatory effect on β cells division and insulin secretion [18,65]. Benzofuranebisindole hybrids have been shown to have in vitro antioxidant effect and in vivo anti-dyslipidemic activity as it decreases total cholesterol, triglycerides and phospholipids through increasing the plasma lecithin cholesterol acyltransferase activity, which plays a key role in lipoprotein metabolism increasing HDL-C in serum level [66].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2b these two extracts both present lipase inhibitory activities in a concentration-dependent manner, indicating a possible likeness in their action mechanism. There are studies indicated that the lipase inhibitory constituents could be better extracted from plants when water be the solvent, compared to methanol (Maqsood, Ahmed, Atique, & Malik, 2017). A great deal of edible Allium from Liliaceae family had been shown to exhibit favorable effects on antiobesity and oxidative stress, such as Allium sativum L. (Kim, Kim, Kim, & Om, 2013), Allium fistulosum L. (Sung, Yoon, Kim, Yang, & Kim, 2011), and Allium cepa L. (Kumari & Augusti, 2007).…”
Section: α-Glucosidase Inhibitory Activitymentioning
confidence: 99%
“…Kondisi obesitas dapat menyebabkan terjadinya kelainan metabolisme lipid yang ditandai dengan kelainan profil lipid dalam plasma seperti kadar kolesterol total yang tinggi, kadar trigliserida yang tinggi, dan kadar kolesterol highdensity lipoprotein (HDL) yang rendah. Absorpsi asam lemak dalam tubuh sebagai langkah awal dalam metabolisme lipid dapat diturunkan dengan menghambat aktivitas enzim lipase pankreas sebagai target antiobesitas (Maqsood et al, 2017;Nomura and Casida, 2016). Kondisi hiperkolesterolemia tentunya akan membaik ketika metabolisme lipid dalam tubuh kembali normal.…”
Section: Pendahuluanunclassified